Characteristics of flexible ZnO nanorod UV photodetectors processed by using a direct silicon etching transfer method. Issue 17 (12th April 2022) - Jang, Hun; Kwon, Do-Kyun; Kim, Do Hoon; Myoung, Jae-Min
Abstract : A flexible UV photodetector based on ZnO NRs with good photoelectrical properties was fabricated by applying DSET to achieve superior UV-sensing properties. Abstract : A simple and sustainable method is presented for producing ultra-thin flexible ultraviolet (UV) photodetectors based on zinc oxide (ZnO) nanorods (NRs) by using a direct silicon etching transfer (DSET) method that allows the transfer of the device from a silicon or glass substrate to various flexible substrates. The DSET method facilitates the transfer of photodetectors to various substrates without the degradation of their properties. The ZnO NR-based UV photodetector transferred to a polyethylene terephthalate (PET) substrate by using this method exhibited excellent UV-sensing properties with a UV on–off ratio of 431 and rise and decay times of 1.08 and 0.69 s, respectively, upon UV exposure under a bias of 2.0 V. In addition, even after repetitive DSET processes, the ZnO NR UV photodetectors exhibited stable UV-sensing properties without appreciable performance degradation. Moreover, the photodetectors transferred on PET substrates by using the DSET method showed stable UV-sensing properties even after 10 000 cycles of bending at a bending radius of 2.5 mm.